Egyptian Women Workers and Entrepreneurs : Maximizing Opportunities in the Economic Sphere - Nasr, Sahar (World Bank, 2012)
Women are a powerful force for sustainable economic growth. A growing body of microeconomic empirical evidence and emerging macroeconomic analysis shows that gender inequality limits economic growth in developing economies. Research also shows that considerable potential for economic growth could be realized if countries support women's full economic participation. Increases in women's income tend to correlate with greater expenditure on family welfare and children, because women often spend a greater share of their income on their children's nutrition, health care, and education. From an economic perspective, removing gender biases and maintaining a level playing field reduces possible market distortions or malfunctioning. Moreover, promoting women's participation in business may bolster women's overall participation in the labor market, because women-owned businesses are more likely to employ other women. This report analyzes the main reasons for this disparity in the Arab Republic of Egypt and proposes solutions to level the playing field and enable women's full economic contributions. The Investment Climate Survey (ICS) of 1,156 enterprises from the manufacturing sector was carried out in October 2008, using the World Bank standard methodology. The recall questionnaire of 566 enterprises was conducted in October 2008. The gender workers module was conducted in August 2005. It sampled about 15 full-time workers from each firm covered by the ICS recall survey. About 70 percent of the ICS sample is made up of small and medium firms, about 85 percent of which are owned by individuals or families. Large firms employing more than 150 workers account for about 30 percent of the sample. In about 35 percent of the sample, a woman is a main shareholder; in 15 percent of these firms, women own the majority of the firm.